Neuropsychiatric Lupus, the Blood Brain Barrier, and the TWEAK/Fn14 Pathway - Putterman, Chaim (Frontiers in Immunology, 2013)
Patients with systemic lupus erythematosus (SLE) can experience acute neurological events such as seizures, cerebrovascular accidents, and delirium, psychiatric conditions including depression, anxiety, and psychosis, as well as memory loss and general cognitive decline. Neuropsychiatric SLE (NPSLE) occurs in between 30 and 40% of SLE patients, can constitute the initial patient presentation, and may occur outside the greater context of an SLE flare. Current efforts to elucidate the mechanistic underpinnings of NPSLE are focused on several different and potentially complementary pathways, including thrombosis, brain autoreactive antibodies, and complement deposition. Furthermore, significant effort is dedicated to understanding the contribution of neuroinflammation induced by TNF, IL-1, IL-6, and IFN-γ. More recent studies have pointed to a possible role for the TNF family ligand TWEAK in the pathogenesis of neuropsychiatric disease in human lupus patients, and in a murine model of this disease. The blood brain barrier (BBB) consists of tight junctions between endothelial cells (ECs) and astrocytic projections which regulate paracellular and transcellular flow into the central nervous system (CNS), respectively. Given the privileged environment of the CNS, an important question is whether and how the integrity of the BBB is compromised in NPSLE, and its potential pathogenic role. Evidence of BBB violation in NPSLE includes changes in the albumin quotient (Qalb) between plasma and cerebrospinal fluid, activation of brain ECs, and magnetic resonance imaging. This review summarizes the evidence implicating BBB damage as an important component in NPSLE development, occurring via damage to barrier integrity by environmental triggers such as infection and stress; cerebrovascular ischemia as result of a generally prothrombotic state; and immune mediated EC activation, mediated by antibodies and/or inflammatory cytokines. Additionally, new evidence supporting the role of TWEAK/Fn14 signaling in compromising the integrity of the BBB in lupus will be presented.